The Effect of Supervision, Information Technology, Motivation, And Workload on Nurses' Performance at Surakarta Islamic Hospital - Arsyadanie Saifi Adli; Istiatin Istiatin; Oong Ridhoi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine and explain the influence of supervision, information technology, motivation, and workload on nurse performance at Surakarta Islamic Hospital. The population of this study was 59 nurses at Surakarta Islamic Hospital, with a total sampling method. Data collection was done using a questionnaire with a Likert scale. The data analysis technique used was multiple linear regression analysis. The results showed that supervision, information technology, motivation, and workload contributed 27.5% to nurse performance, while the remaining 72.5% was explained by other variables not examined in this study. The recommendation of this study is that Surakarta Islamic Hospital should develop a coaching-based supervision system, improve the implementation of information technology, integrate professional performance and Islamic values, and conduct regular surveys on workload. Keywords:Nurse Performance, Supervision, Information Technology, Motivation, Workload